Dicephalic Monstrosity in a Heifer - ABRAHAM, JOHN; BIHU, S; RAJ, INDU V; LAKSHMANAN, BINDU (The Indian Journal of Animal Reproduction, 2007)
A 3 ½ year old crossbred heifer with normal gestation and prolonged labour pain was presented. Obstetrical examination revealed a craniophagus dicephalic foetus. Caesarian section was resorted to deliver a live female dicephalic monster. The anatomical structure of the monster is described and discussed.